EXPLORING THE CONTRIBUTION OF PRINT MEDIA TO THE ISLAMIC RENEWAL MOVEMENT: A HISTORICAL REVIEW - Tamami, Fauziyah Qurrota A’yun; Jinan, Mutohharun; Rahmawati, Siti (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This study aims to determine the contribution of print media to the Islamic renewal movement from the perspective of al-urwatul wustqa, al-manar, al-imam, and al-munir, as well as the contribution of the voice of Muhammadiyah as a derivative of Al-Manar magazine. This article reviews the important role of print media in the Islamic renewal movement, especially through magazines such as al-urwatul wustqa, al-manar, al-imam, and al-munir. Through qualitative research methods of a type of literature study with a descriptive nature of analysis using data from related literature, this article highlights how the four magazines spread ideas of renewal, educated the public, and built awareness about Islamic teachings in accordance with the demands of the times. This research shows that this print medium has made a significant contribution to re-exploring the universal message of Islam in the context of the new age and disseminating it comprehensively. Suara Muhammadiyah is identified as a continuation of the spirit of renewal brought by Al-Manar, a magazine that has an important role in the Islamic renewal movement in Indonesia. The main focus of Suara Muhammadiyah is to spread the ideas and efforts of Islamic renewal that have been carried out by the Muhammadiyah Association. Suara Muhammadiyah also serves as a means to raise the importance of education, the unity of Muslims, and the relevance of Islam in modern life.